Explanation of Nationalism Feelings in the Creation of Novels (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The work of the progressive Mahmudhodji Behbudi was studied in the article. Bekhubudi was open in his home and taught the country for free. He used educational methods in the field of education in the educational system. It is studied to teach Turkish children, to give them practical advice, and to give them practical advice in their dress and gait.